2011
DOI: 10.1186/1478-7954-9-13
|View full text |Cite
|
Sign up to set email alerts
|

Healthy life gains in South Australia 1999-2008: analysis of a local Burden of Disease series

Abstract: BackgroundThe analysis describes trends in the levels and social distribution of total life expectancy and healthy life expectancy in South Australia from 1999 to 2008.MethodsSouth Australian Burden of Disease series for the period 1999-2001 to 2006-2008 and across statistical local areas according to relative socioeconomic disadvantage were analyzed for changes in total life expectancy and healthy life expectancy by sex and area level disadvantage, with further decomposition of healthy life expectancy change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…Second, it has been increasing number of countries which measure HALE at their national level (9101112131415). HALE can be used in a variety of policy applications such as measuring the quality of life and monitoring disparity (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, it has been increasing number of countries which measure HALE at their national level (9101112131415). HALE can be used in a variety of policy applications such as measuring the quality of life and monitoring disparity (20).…”
Section: Discussionmentioning
confidence: 99%
“…Also, they are focusing and monitoring on the main influence factors on HALE such as chronic conditions, health behaviors, and socio-economic and environmental factors (23). In case of Australia, they analyzed the annual trends in the levels and social distribution of LE and HALE (12). One Canadian research indicated that body mass index can affect on LE and HALE (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the advantages of HALE discussed above, decomposition of changes in HALE over time into the contributions of diseases and injuries has the potential to help researchers and policy makers to better understand the changes in population health, to identify health policy priorities, and to provide more evidence on epidemiological transition theory. However, only two studies in Australia have been conducted on the subject, and they used analyses at disease group level or for selected diseases 1415. Therefore, this study aimed to decompose the changes in HALE at birth (HALE 0 ) from 1990 to 2013 into the contribution of 306 diseases and injuries for the globe, 21 regions, and 187 countries.…”
Section: Introductionmentioning
confidence: 99%
“…1 Disability-free life expectancy gained from elimination of diseases and injuries was proposed as an indicator of disease burden and has been investigated in several countries. 1 – 6 …”
Section: Introductionmentioning
confidence: 99%